2017
DOI: 10.1128/iai.00046-17
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Cellular Exit Alters Interactions with Host Dendritic Cells

Abstract: The strategies utilized by pathogens to exit host cells are an area of pathogenesis which has received surprisingly little attention, considering the necessity of this step for infections to propagate. Even less is known about how exit through these pathways affects downstream host-pathogen interactions and the generation of an immune response. Chlamydia trachomatis exits host epithelial cells through two equally active mechanisms: lysis and extrusion. Studies have characterized the outcome of interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…HeLa and McCoy cells were infected with wild type C. trachomatis L2 or chimera strains and analyzed for phosphatidylserine externalization and caspase 3/7 activation using the Annexin V Alexa Fluor 594 and Image-iT live caspase 3/7 assay kits (Molecular Probes), respectively, using established procedures (Sherrid & Hybiske, 2017).…”
Section: Apoptotic Assaysmentioning
confidence: 99%
“…HeLa and McCoy cells were infected with wild type C. trachomatis L2 or chimera strains and analyzed for phosphatidylserine externalization and caspase 3/7 activation using the Annexin V Alexa Fluor 594 and Image-iT live caspase 3/7 assay kits (Molecular Probes), respectively, using established procedures (Sherrid & Hybiske, 2017).…”
Section: Apoptotic Assaysmentioning
confidence: 99%
“…Furthermore, results showed that survival of C. trachomatis was significantly lower when infecting macrophages or DCs compared to epithelial cells (Steele et al, 2004). However, the group of Hybiske has proven that bone marrow macrophages as well as DCs engulf extrusions and that subsequent survival of chlamydiae is hence promoted by the lipid barrier surrounding them (Sherrid and Hybiske, 2017; Zuck et al, 2017). Nevertheless, the engulfment of extrusions initiated fast DC apoptosis and significantly modified the transcriptional upregulation of biologically relevant DC cytokines (Sherrid and Hybiske, 2017).…”
Section: Chlamydial Transport Through the Host Cellmentioning
confidence: 99%
“…However, the group of Hybiske has proven that bone marrow macrophages as well as DCs engulf extrusions and that subsequent survival of chlamydiae is hence promoted by the lipid barrier surrounding them (Sherrid and Hybiske, 2017; Zuck et al, 2017). Nevertheless, the engulfment of extrusions initiated fast DC apoptosis and significantly modified the transcriptional upregulation of biologically relevant DC cytokines (Sherrid and Hybiske, 2017). Hybiske and Stephens also claimed that both processes, extrusion and lysis, are prevalent among genital as well as LGV biovars of C. trachomatis and that they occur at nearly equivalent frequencies (Hybiske and Stephens, 2007), thus objecting the papers of Banks et al (1970) and Todd and Caldwell (1985).…”
Section: Chlamydial Transport Through the Host Cellmentioning
confidence: 99%
“… 2017 ). While this process enabled enhanced pathogen survival in the phagocytes, likely by preventing phagocyte activation, and was suggested to enable the bacteria to exploit these cells as vehicles for dissemination, it did only infrequently result in productive infection of the phagocytes (Sherrid and Hybiske 2017 ; Zuck et al . 2017 ).…”
Section: Pro-death Activities Of Chlamydiaementioning
confidence: 99%